Search for neutral Higgs bosons of the minimal supersymmetric standard model in pp collisions at √s = 8 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Colombo, Tommaso; Davygora, Yuriy; Dietzsch, Thorsten; Djuvsland, Julia Isabell; Dunford, Monica; Giulini, Maddalena; Hanke, Paul; et al. (Journal of high energy physics, 2014)
A search for the neutral Higgs bosons predicted by the Minimal Supersymmetric Standard Model (MSSM) is reported. The analysis is performed on data from proton-proton collisions at a centre-of-mass energy of 8 TeV collected with the ATLAS detector at the Large Hadron Collider. The samples used for this search were collected in 2012 and correspond to integrated luminosities in the range 19.5-20.3 fb−1. The MSSM Higgs bosons are searched for in the τ τ final state. No significant excess over the expected background is observed, and exclusion limits are derived for the production cross section times branching fraction of a scalar particle as a function of its mass. The results are also interpreted in the MSSM parameter space for various benchmark scenarios.
Gesehen am 19.01.2021